G57(P) Gamification: Student feedback and creation of bespoke board games. (24th May 2017) - Webb, M; Henderson, B
Abstract : Educational games are well researched in many disciplines in relation to pedagogical value. The authors summarise the involvement, creation and playing of clinical practice simulation board games. Outcomes following the introduction of the original ward management simulation game included: Dynamic, evidence based decision-making experience of real case vignettes, integrating theory to practice The facilitation of an enjoyable, competitive atmosphere in which the realities of change and uncertainty were explored in a low risk setting Safe experiential learning of the leadership, team working and time management attributes valued when negotiating for individual patient/client advocacy in practice Students creating and playing their own games that included education and practice partnership working The authors explore the validity of educational games as effective learning tools that underpin unit learning outcomes and student motivation. Educational games also assist with student creativity and lead to education-practice learning. The original ward management simulation game has been trialled with children's nursing students in their 3 rd year and helped them consider ward management and delegation. The board was then redesigned and utilised with 3 rd year adult nursing students, utilising adult based scenarios. New cards were then developed for use with 2 nd year adult/child/mental health students to assist them in learning about leadership. A mental health board and scenario cards are in development. Other games have also been developed by the students as an intervention to facilitate collaborative student engagement, critical analysis and critical decision making. The authors aim to attract those who already use, or wish to use simulation games as either 'introductory, strategic or specialist' facilitative tools in the learning process. They aim to explore the effectiveness of games as a learning resource, the student role in their creation and evaluation, the challenges associated with moving from concept to the table and how support and solutions were found in linking education and practice partnership learning.